Traditional Timber Housing Structure in Zeyrek - Akcabozan, Aylin (SPRINGER INTERNATIONAL PUBLISHING AG, 2016)
Zeyrek, as a World Heritage Site and one of the important residential areas of the old city of Istanbul, has a significant number of historical timber houses belonging to late 19th-early 20th century. Due to its topographical, climatic, social, economic and cultural features as well as its nearby wooded environment, local materials and traditional technology, Zeyrek has reflected a precious architectural pattern consisting of many of timber-framed buildings for a long time. This paper examines traditional architecture, presents and promotes the experience with timber housing restoration in Zeyrek, Istanbul, aiming to analyze the existing wooden housing pattern in the area and to investigate the restitution and restoration project of a traditional timber house in detail. The conservation and restoration process in the traditional structure of wood extracted positive lessons of history. In this context, the classification of physical characteristics commonly found in these timber housing settlement has been done considering the method of construction, the facade proportions of the elements, plan schemes, articulation of different forms, the conservation and restoration projects in the site. The present study follows methodological principles of historical research about Zeyrek. A case study about traditional timber house structure consists of field surveys and documentation. According to observation and analysis of the traditional housing settlement, the main classifications were obtained, along with photographical survey showing the current situation of the timber housing characteristics of the site. The paper focuses on this transformation by putting forward integrated conservation approach.
Keywords: Traditional housing; Timber structures; Integrated conservation; Zeyrek; Construction & Building Technology; Engineering